Should physicians routinely be involved in the care of elderly surgical patients? Yes. (4th March 2011) - Wilkinson, Kathy; Wilson, Helen
Abstract : Standards of care for elderly people in hospital have come under the spotlight. Kathy Wilkinson and Helen Wilson believe that geriatricians can help improve the management of surgical patients, but Barbara Herd (doi:10.1136/bmj.d1072 ) is concerned that the dilution of resources will harm those who most need specialist attention